De la relation entre le positionnement épistémologique d’un chercheur et ses représentations relatives à l’écriture de la recherche. Amorce d’une réflexion méta-didactologique - Izabela Orchowska (Studia Romanica Posnaniensia)
This paper explores the dialogical relationship between a researcher’s epistemological stance and his representations of research writing in the field of language and culture didactics. It emphasizes the importance of considering the relationship of these two processes in the professional development of novice researchers. Drawing on the epistemological aspects of the French conception of foreign language didactics fr. didactique-didactologie des langues-cultures), understood as an autonomous academic discipline, the author analyses meta-didactic papers by two French scholars Christian Puren and Véronique Castellotti. The analysis corroborates the influence of the researchers’ epistemological stances on their representations of research writing within the discipline.